2021
DOI: 10.1111/cen.14393
|View full text |Cite
|
Sign up to set email alerts
|

Syndromic Forms of Hyperinsulinaemic Hypoglycaemia—A 15‐year follow‐up Study

Abstract: Objective Hyperinsulinaemic hypoglycaemia (HH) is one of the commonest causes of hypoglycaemia in children. The molecular basis includes defects in pathways that regulate insulin release. Syndromic conditions like Beckwith‐Wiedemann (BWS), Kabuki (KS) and Turner (TS) are known to be associated with a higher risk for HH. This systematic review of children with HH referred to a tertiary centre aims at estimating the frequency of a syndromic/multisystem condition to help address stratification of genetic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…Over 28 different syndromes which feature HI have been reported with the most common being Beckwith-Wiedemann syndrome (BWS) and Kabuki syndrome ( 33 ) ( Table 2 ). The proportion of individuals with syndromic disease who present with HI varies between genetic subgroups.…”
Section: Genetic Types Of Congenital Hyperinsulinismmentioning
confidence: 99%
“…Over 28 different syndromes which feature HI have been reported with the most common being Beckwith-Wiedemann syndrome (BWS) and Kabuki syndrome ( 33 ) ( Table 2 ). The proportion of individuals with syndromic disease who present with HI varies between genetic subgroups.…”
Section: Genetic Types Of Congenital Hyperinsulinismmentioning
confidence: 99%
“…Diazoxide choline controlled-release tablets have been reported to be useful in controlling hyperphagia, obesity and aggressive behaviors in cases with Prader-Willi syndrome [ 210 , 211 ]. This drug has also been reported to prevent the aggravation of the pre-existing ID/GDD for the cases with syndromes known to be accompanied with hyperinsulinaemic hypoglycaemia such as Beckwith-Wiedemann, Sotos, Kabuki and Turner [ 212 ]. The early initiation of the diazoxide within 3 months of the onset of symptoms is associated with normal intelligence [ 213 ].…”
Section: Summary Of the Clinical Featuresmentioning
confidence: 99%
“…However, in a minority of cases with BWS, hypoglycemia is more severe and persistent, showing the characteristics of CHI. Some patients are responsive to diazoxide ( 12 ) and some may even require pancreatic surgery ( 12 14 ). The overall prevalence of clinically significant and persistent CHI in BWS has not been determined, but is probably less than 10% ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that most of the patUPD11p patients without a paternally inherited K ATP channel mutation do not require treatment beyond 2 years of age ( 12 , 14 ). This might be related to the shift of KCNQ1 expression from monoallelic fetal to biallelic adult expression ( 21 ).…”
Section: Resultsmentioning
confidence: 99%